Effect of Levels and Times of Application of Super Micro Plus Nanofertilizer on Sugar Yield and Quality of Sugarcane Juice, Saccharum Officinarum L. Under the Conditions of the Central Region of Iraq - Alghargan, Nidhal Y.A. (International Journal Papier Advance and Scientific Review, 2023)
The experiment was carried out according to a completely randomized block design with three replications, and the data were analyzed statistically, and the results showed the following; (1) The use of nanofertilizer at the level of 2 g.l ̄¹ resulted in a significant increase in all the studied characteristics represented in number of milling stems, the percentage of sucrose, the percentage of total dissolved solids, the percentage of juice purity, the stems yield , and the sugar yield, as it reached 54.9 stems.m ̄¹, 15.4%, 17.5%, 88.04%, and 61.5 tons.ha ̄ ¹ and 9.34 tons.ha ̄¹ respectively; (2) The spraying of nanofertilizer at the beginning of the tillering stage resulted in a significant increase in most of the studied characteristics represented in mean number of milling stems, the percentage of sucrose, the percentage of total dissolved solids, the stems yield, and the sugar yield, reaching 57.1 stems.m ̄¹ , 14.1%, 17.2%, and 53.6 tons.ha ̄¹ and 7.63 tons.ha ̄ ¹ respectively .While spraying the nanofertilizer at the beginning of the elongation stage showed a significant increase in juice purity amounted to 84.68%, Compared to the fertilizer application at the beginning of the tillering stage and the beginning of the maturity stage, which recorded 81.85 and 83.51%, respectively; (3) Spraying the plants with nanofertilizer at the level of 2 g.l ̄¹ at the beginning of the tillering stage resulted in achieving the highest increase in each of the number of milling stems, the percentage of sucrose, the percentage of total dissolved solids, the percentage of juice purity, the stems yield, and the sugar yield, as it reached 62 stems.m ̄¹ ,16.3%, 18.0%, 90.50%, and 66.0 tons.ha ̄ ¹ and 10.30 tons.ha ̄ ¹ respectively.